Avaliação da fitotoxicidade e citogenotoxicidade de lodo gerado no tratamento de efluentes têxteis utilizando Allium cepa L. - Barbosa, Lenise Marques Da Silva (2016)
The textile industry is considered an important sector of the Brazilian and the world’s economy, presenting considerable growth in the last years. During the production processes, great amount of high complexity industrial residues is generated. The complexity of the relations between the chemical compounds and the biota, the unfamiliarity of all the constituents of the sludge, associated to possible effects of the interactions between their components, demonstrate that estimating the toxicity of this kind of residue just through chemical analyses is insufficient. One of the alternatives for this issue is the use of plant bioassays. Within this context, the aim of this work was to test the toxicity of sludge samples from a textile industry using the phytotoxicity and cytogenotoxicity assays with Allium cepa L. seeds and bulbs. For this, five aqueous extracts obtained from 4 sludge samples, with a fifth sample composed by a mixture from the other 4 ones, in equal parts. The chemical characterization of each sample was performed. The phytotoxicity in seeds was evaluated using the parameters: percentage of germination (% G), germination rate (IVG), number of normal plants (NP), root elongation (AR), length of the aerial part (CPA) and production of fresh biomass (BF). In bulbs the phytotoxicity was assayed through the number (NR) and the growth of roots (CR). The cytogenotoxicity was evaluated by the mitotic index and chromosomic abnormalities in roots from A. strain seeds and bulbs. The data were submitted to the variance analysis and the means were compared by the Scott-Knott test at 5% significance. High concentration of chrome was verified in sample 1, displaying higher value than the other samples (1312,4 mg kg-¹). In general the extracts from the samples did not present phytotoxicity or just subtle deleterious effects, except for the extract from sample 1, which showed high phytotoxicity observed by the parameters % G, IVG, AR and CPA. Either the phytotoxics or the cytogenotoxics seem to be related mainly to the high concentration of chrome. The inhibition of the mitotic index (IM), the high frequency of micronucleus (MN), as well as total high rate of chromosomic abnormalities found in the extracts from the samples, in assays with either seeds or bulbs, demonstrated the cytogenotoxicity of the textile sludge. The parameters of cytogenotoxicity were more suitable than those of phytotoxicity for the ecotoxicologic evaluation of this kind of residue. A. strain seeds were more sensitive when compared to bulbs, for evaluating the cytogenotoxic effects of the samples.